2019
DOI: 10.1080/14786419.2019.1698576
|View full text |Cite
|
Sign up to set email alerts
|

Phloroglucinol derivatives from Hypericum species induce in vitro proliferation of cells involved in the wound healing process

Abstract: The genus Hypericum (Hypericaceae) is a recognized source of therapeutic agents, being some species widely used due to their wound healing properties. In a previous study, south Brazilian species H. caprifoliatum, H. carinatum, H. connatum, H. myrianthum and H. polyanthemum demonstrated potential to induce proliferation of keratinocytes. In the present study, the effect of phloroglucinol derivatives isolated from Hypericum on cell proliferation of human keratinocytes, fibroblasts and stem cells was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The results mentioned above have shown the interesting skin cancer treatment properties of these biomolecules, with no significant cytotoxic effect (Bridi et al, 2019(Bridi et al, , 2017.…”
Section: Cytotoxicity and Photodynamic Therapymentioning
confidence: 89%
“…The results mentioned above have shown the interesting skin cancer treatment properties of these biomolecules, with no significant cytotoxic effect (Bridi et al, 2019(Bridi et al, , 2017.…”
Section: Cytotoxicity and Photodynamic Therapymentioning
confidence: 89%
“…TV and HO are frequently used in traditional medicine due to their tissue repair-accelerating effect [18,19]. TV and HO induce the active cells in wound healing process, especially fibroblast and endothelium, and thus, affect wound healing [18,20]. Thus, the fact that TM perforations can also have positive effects on the healing process should not be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts of Hypericum perforatum and Azadirachta indica show effects in different kinds of dermatological conditions. [10][11][12] Increasing knowledge about pharmacological activities of its characteristic ingredients, such as hypericin and hyperforin, has given new impetus to investigate the potential of topical preparations in dermatological problems of current interest such as skin diseases like atopic dermatitis, psoriasis, herpes infections, nonmelanoma skin cancer and last but not least in skin care. 10 Different types of skin wounds like surgical wounds, 3,9 burns, 4,13 diabetic foot ulcers, 7,8,14 vascular/venous ulcers, pressure sores 15 and calcinosis-related skin ulcers 16 also seem to respond to the pharmacological active ingredients of Hypericum perforatum and Ayadirachta indica oil.…”
Section: Discussionmentioning
confidence: 99%
“…16 Bridi et al re-cently showed the in vitro capacity of phloroglucinol derivatives from Hypericum species to induce proliferation of cells involved in the wound healing process, therefore reinforcing the importance of Hypericum species as potential source of wound healing compounds. 12 Being a simple wound dressing, no specific training or equipment is required. Hypericum perforatum and Neem oil therefore might be of use as an additional, simple and cost-effective local treatment option in non-healing wounds.…”
Section: Discussionmentioning
confidence: 99%